Deconstructing Symbols and Meanings in the Kecak Dance - Alit Sankara (Bali Tourism Board, 2023)
Initially, tourists visited the village where the group resided to witness the Kecak dance. However, the dance's popularity grew, and it became a feature in various events. Tourists could now enjoy Kecak performances at destinations like Uluwatu, Tanah Lot, Batubulan, and others, which provided dedicated spaces for these performances. The Kecak dance, born out of creative cultural expression, became a unique art form showcased specifically for tourists. The choreography in Kecak dance is divided into five parts. In this choreography, all elements in the Kecak performance interact, creating a message directed to the audience. In dramaturgical analysis, it's important to note that Kecak Dance focuses on the aspects of performing arts. It is a dance highly specific to Balinese culture with unique characteristics reflecting their identity and cultural heritage. In the analysis of the staging of Kecak Dance using Symbolic Interactionism Theory, it portrays human life from a Hindu perspective consisting of Suka (joy), Duka (sorrow), Lara (pain), and Pati (death). The characters in Ramayana represent the qualities of protagonists and antagonists, which then interact with each other, giving rise to new universal values, such as Loyalty. Understanding the message in Kecak dance can be enhanced by increasing the involvement of tour guides as providers of additional information to tourists. Additionally, providing brochures containing synopses of the Ramayana story or the plot of Kecak dance in foreign languages during the performance can help the audience understand the presentation more easily, allowing the art to be fully appreciated.